Produção de Pereira: manejos da planta e vascularização do xilema. - Silva, Juliana Bertolino da (2009)
A major limitation to the expansion of the pear culture cultivated under mild winter, as South of Brazil, is the cultivar adaptation. During the winter, the temperature fluctuation and low accumulation of cold have been reported by some authors as cause of floral button abortion. Moreover, the pear fruit satisfactorily when well managed, being the pruning and girdling one of the main fruiting techniques. This work aimed to evaluate the responses by pear cultivars to different cultural practices in order to increase the fruit an production and to evaluate the development of xylem vessels during dormancy. The work was carried out in two stages: the first in Brazil at the Federal University of Pelotas and the second in Italy, Faculty of Agriculture, in Pisa. In Garber cultivar, the treatments were: 1- control 2- short summer pruning 3- arching of branches and long summer pruning and 4 arching of branches in the winter, 5 - winter pruning; 6 girdling of branches, 7 Promalin ® and 8 - Biozyme * TF. For the cultivars Shinseiki and Housui, the treatments were: 1 - control, 2 - trunk girdling in April 3 - ringing branches in April. To Kousui, the treatments were: 1 trunk girdling, 2 - branch girdling + pruning 3- pruning, 4- branch girdling 5-control. For the Conference, the healthy and intact branches of plants were marked and followed during the dormancy period, the continuity of vascular bundles between the branches and the buds were observed in the stereomicroscope and the histological evaluations were observed under a fluorescence microscope. All cultivars responded to the blinding technique. For the Garber the effective fruit is influenced by the treatments when assessed in different fruiting bodies. The fruiting body which showed the highest rates of fruit were brindila coronada and bourse. For the Shinseiki cv, the trunk girdling increased the effective fruiting and the production per trunk area. In the cultivar Housui, the branches girdling increased the fruiting but not the production. In the cultivar Kousui the treatments with blinding increased the effective fruiting, the maturation was anticipated and increased the soluble solid content. In the cultivar Conference, through the vascular connections, it can establish stages of dormancy during the bud flowers evolution, as well as to establish that 1,000 chilling hours are needed to overcome endodormancy.